Os valores das notícias e a fonte de informação: o discurso da elite e a personalização na imprensa digital - Mañoso-Pacheco, Lidia (Texto Livre, 2020)
This paper proposes a corpus-based examination of the discourse of eliteness and personalisation news values in the information source. To that end, the study compares digital news in British and Spanish corpora. The results reveal a tendency to quote elites, which are frequently constructed by means of recognised names from politics, inanimate references with broad scope and role labels in apposition. To a lesser extent, prestige is construed through status-indicating modifiers and allusion to place of work. Ordinary sources, however, are usually construed via indication of provenance, reference to family relationship and anaphoric allusions, mostly in British sources. It remains to be clarified whether the construal of these values is in consonance with the editorial stance of the newspaper.